Review of Maslahah Mursalah and Consumer Protection Laws on Traditional Dental Practices - Tasyabilah, Nurus; Karim, Busro; Dzikrulloh, Dzikrulloh (Et-Tijarie, 2023)
This research is field research to know how dental artisans practice at Pink Behel Sukodono Sidoarjo, which will then be analyzed based on maslahah mursalah theory and Law Number 8 of 1999 concerning Consumer Protection. This research uses qualitative research for the type of field research (field research), which is descriptive-analytical. The approach method used is normative-empirical juridical. In the research process, researchers use primary data obtained directly through observation, interviews, documentation, and secondary data to complement the data. Then, the researcher analyzes the data using the inductive analysis method. This study's results prove that the Dental Practice at Pink Behel Sukodono Sidoarjo needs a license from the health office and the Sidoarjo district/city government. When viewed from the theory of maslahah mursalah, the practice of Dental Practice is included in the mas{lahah tahsiniyyat. During their practice, no consumers have been harmed by Dental Practice; if the benefits are greater than the mafsadat that will be generated, then attracting benefits is far more prioritized than rejecting mafsadat. Viewed from Consumer Protection Law, Dental Practice at Pink Behel Sukodono Sidoarjo violated Article 4 letter (a) regarding consumer rights to security and safety in consuming goods and services, and Article 7 paragraph (2) does not provide correct, clear, and honest information to consumers, so that it is very risky to harm and if a consumer is harmed then the Dental Practice must provide compensation as stipulated in Article 19. Dental Practice also exceeds the limits of their authority in working as stipulated in the Regulation of the Minister of Health Number 39 of 2014 concerning Guidance, Supervision, and Licensing for Dental Practice Work.